THE INFLUENCE OF CAPITAL, SEEDLINGS, LAND AREA, AND LABOR ON RUBBER PLANT PRODUCTION IN WEST WOYLA DISTRICT - Yulia Windi Tanjung; Nafa Rahmalia; Rony Rahmat Hidayat Hasibuan; Fantashir Awwal Fuqara; Hartini; Siti Aminah (LPPM Universitas Malikussaleh - Indonesia, 2026)
Inadequate capital, poor-quality seedlings, a lack of land area, and a shortage of trained labour for managing rubber plantations are the primary issues facing rubber growers in the West Woyla District. This research aims to analyze the influence of capital, seedlings, land area, and labor on rubber plant production in West Woyla District. The research method used is a quantitative descriptive method. The sampling method used is the Slovin formula, resulting in 97 rubber farmers. Data collection was conducted thru interviews using questionnaires, observations, and documentation. The data analysis method uses Multiple Linear Regression analysis as well as T-test and F-test using SPSS 20 software. The R Square value of 0.702 indicates that 70.2% of rubber production in West Woyla Regency is explained by Capital, Land Area, Seeds, and Labor, while the remaining 29.8% is influenced by other factors. Simultaneously, these variables have a significant effect on production, as shown by the calculated F value (54.233) being greater than the F table value (2.470). Partially, Capital (0.025), Land (0.000), Seedlings (0.004), and Labor (0.005) all have significance values below 0.05 with positive coefficients, each variable has a positive and significant effect on production. Keywords: Capital, Labor, Land Area, Rubber Plant Production, Seedlings.